Neoantigen-specific T cell help outperforms non-specific help in multi-antigen DNA vaccination against cancer - Joanna Fréderique de Graaf; Tamara Pesic; Felicia S. Spitzer; Koen Oosterhuis; Marcel G.M. Camps; Iris Zoutendijk; Bram Teunisse; Wahwah Zhu; Tsolere Arakelian; Gerben C. Zondag; Ramon Arens; Jeroen van Bergen; et al. (Molecular Therapy: Oncology)
CD4+ T helper antigens are essential components of cancer vaccines, but the relevance of the source of these MHC class II-restricted antigens remains underexplored. To compare the effectiveness of tumor-specific versus tumor-unrelated helper antigens, we designed three DNA vaccines for the murine MC-38 colon carcinoma, encoding CD8+ T cell neoantigens alone (noHELP) or in combination with either “universal” helper antigens (uniHELP) or helper neoantigens (neoHELP). Both types of helped vaccines increased the frequency of vaccine-induced CD8+ T cells, and particularly uniHELP increased the fraction of KLRG1+ and PD-1low effector cells. However, when mice were subsequently injected with MC-38 cells, only neoHELP vaccination resulted in significantly better tumor control than noHELP. In contrast to uniHELP, neoHELP-induced tumor control was dependent on the presence of CD4+ T cells, while both vaccines relied on CD8+ T cells. In line with this, neoHELP variants containing wild-type counterparts of the CD4+ or CD8+ T cell neoantigens displayed reduced tumor control. These data indicate that optimal personalized cancer vaccines should include MHC class II-restricted neoantigens to elicit tumor-specific CD4+ T cell help.